2017
DOI: 10.18869/acadpub.jbrms.4.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of HIV, hepatitis B and C infections among volunteer blood donors at the blood transfusion center of Ilam city, Iran

Abstract: Introduction: Blood derived products have been known as an effective treatment for many years. However, this treatment is not without risk of infections transmission including hepatitis B virus (HBV) and hepatitis C virus (HCV) and human immune-deficiency virus (HIV) in people who received the blood. Nevertheless, due to a high risk of blood born diseases through blood transfusion, screening for these viruses according to the World Health Organization (WHO) is mandatory. The main aim of this research was to as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
1

Year Published

2020
2020
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 7 publications
0
1
1
Order By: Relevance
“…The frequency of blood‐borne pathogens including HBV and HCV was usually lower in females than males 5,34,35 . In the current study only two HBV DNA cases were reported in females by fractionator.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The frequency of blood‐borne pathogens including HBV and HCV was usually lower in females than males 5,34,35 . In the current study only two HBV DNA cases were reported in females by fractionator.…”
Section: Discussioncontrasting
confidence: 58%
“…The blood borne pathogens were reported in regular and repeat blood donors but almost always pose a lower risk of infectious donations than first time blood donors. Blood safety of regular and repeat blood donors was well documented in different studies 5,20,32–34 …”
Section: Discussionmentioning
confidence: 99%